Rapid reduction of antibodies and improvement of disease activity by immunoadsorption in Chinese patients with severe systemic lupus erythematosus. Issue 9 (September 2016) - Huang, Jinxian; Song, Guoxiang; Yin, Zhihua; He, Weizhen; Zhang, Lijun; Kong, Weihong; Ye, Zhizhong
Abstract This was an exploratory analysis comparing the safety and efficacy of immunoadsorption (IAS) combination therapy in severe systemic lupus erythematosus (SLE) receiving corticosteroid pulse and immunosuppressant treatment. Patients enrolled all had predominant organ involvement including proteinuria, thrombocytopenia, pericardial effusion, and cerebral involvement requiring corticosteroid pulse treatment. Fifty-two patients in study group received IAS plus corticosteroid and cyclophosphamide treatment. Fifty-two patients in non-IAS group received corticosteroid and cyclophosphamide treatment. Outcome measurement included C3, dsDNA, AnuA, and SLE disease activity index (SLEDAI) 2k score and in particular cases, proteinuria quantification and platelet count. Disease activity dropped significantly in both groups. Improvement of disease activity markers was more significant in study group than that in non-IAS group. The lower dosage of steroid in study group suggested the steroid-sparing effect of IAS. No severe adverse effect occurred during IAS. Our study suggested IAS as an additional therapy to steroid pulse and immunosuppressant in treating severe SLE.